1). √4 + √49 – √162). √64 + √25 – √93). √64 + √64 – √9 × √16​

Posted on

1). √4 + √49 – √162). √64 + √25 – √93). √64 + √64 – √9 × √16​

No. 1

 sqrt{4} + sqrt{49} - sqrt{16}

 = sqrt{2 times 2} + sqrt{7 times 7} - sqrt{4 times 4}

 = sqrt{2^{2 }} + sqrt{7^{2 }} - sqrt{4^{2 }}

 = sqrt{2^{cancel{ 2}}} + sqrt{7^{cancel{2 } }} - sqrt{4^{cancel{2 } }}

 = 2 + 7 - 4

 = 9 - 4

 = 5

No. 2

 sqrt{64} + sqrt{25} - sqrt{9}

 = sqrt{8 times 8} + sqrt{5 times 5} - sqrt{3 times 3}

 = sqrt{8^{2 }} + sqrt{5^{ 2}} - sqrt{3^{2 }}

 = sqrt{8^{ cancel{2 }}} + sqrt{5^{cancel{2 } }} - sqrt{3^{cancel{ 2}}}

 = 8 + 5 - 3

 = 13 - 3

 = 10

No. 3

 sqrt{64} + sqrt{64} - sqrt{9} times sqrt{16}

 = sqrt{8 times 8} + sqrt{8 times 8} - sqrt{3 times 3} times sqrt{4 times 4}

 = sqrt{8^{ 2}} + sqrt{8^{2 }} - sqrt{3^{2 }} times sqrt{4^{2 }}

 = sqrt{8^{ cancel{2 }}} + sqrt{8^{cancel{ 2}}} - sqrt{3^{cancel{2 } }} times sqrt{4^{cancel{2 } }}

 = 8 + 8 - 3 times 4

 = 8 + 8 - (3 times 4)

 = 8 + 8 - 12

 = 16 - 12

 = 4

1). √4 + √49 – √16 = 5

▶️ √4 + √49 – √16

▶️ 2 + 7 – 4

▶️ 9 – 4

▶️ 5 ✔️

2). √64 + √25 – √9 = 10

▶️ √64 + √25 – √9

▶️ 8 + 5 – 3

▶️ 13 – 3

▶️ 10 ✔️

3). √64 + √64 – √9 × √16​ = 4

▶️ √64 + √64 – √9 × √16

▶️ 8 + 8 – 3 × 4

▶️ 16 – 12

▶️ 4 ✔️

ÄÑẞWÉR B¥ :

●▬▬▬▬▬▬ஜ۩۞۩ஜ▬▬▬▬▬▬●

░ — MØDBRÃÍÑLYÂÇTÏVÉGÄÑẞ — ░

●▬▬▬▬▬▬ஜ۩۞۩ஜ▬▬▬▬▬▬●